DAMPAK KONFLIK ISRAEL DAN PALESTINA TERHADAP POLITIK HUKUM KEBIJAKAN INDONESIA - AGUNG SETIAWAN; RACHMAN MAULANA KAFRAWI; MUH. ALFIAN FALLAHIYAN; RAHMADANI RAHMADANI (GANEC SWARA, 2024)
The aim of this research is to determine the impact of the Israeli and Palestinian conflict on Indonesian legal politics. To obtain quality research results, the method used in this research is a normative-empirical legal research method. Where research examines regulations related to agrarian law regulation and expert opinions (law in the book), as well as looking at its implementation through the media (the Israeli – Palestinian conflict in the field) in order to find out how it is implemented in the field (law in action). In order to make this research easier, this research uses a statutory approach (legislative approach), a contextual approach (conceptual approach) and a sociological approach (sociological approach). The resulting research results are that no life is worth dying for purely political interests (territory of the country), Israel and Palestine must find a solution to sit down together so that there are no more conflicts and victims. Psychologically, Indonesia supports Palestinian sovereignty, while also trading with Israel. Indonesia is a country with a middle position and is expected to become a mediator for peace between Israel and Palestine